Organobimetallic Nickel‐Iron Complexes, Valence Tautomer or Charge Localized Ferrocene Ligands Upon Oxidation. Issue 5 (27th January 2022) - Ringenberg, Mark R.; Schnierle, Marc; Sondermann, Christina
Abstract: [[CpNi(dRpf)] + (dRpf=1, 1'‐bis(di‐R‐phosphino)ferrocene, R=phenyl (dppf) [1] +, iso ‐propyl (dippf) [2] +, and cyclohexyl (dcpf) [3] + ), CpNi(dRpf)] + (dRpf=1, 1'‐bis(di‐R‐phosphino)ferrocene, R=phenyl (dppf) [1] +, iso ‐propyl (dippf) [2] +, and cyclohexyl (dcpf) [3] + ), showed two reversible electrochemical processes, one cathodic and one anodic in the cyclic voltammogram. CpNi I was generated in the cathodic processes for all three complexes, while spectroscopic data and dft analysis for the anodic process suggested contributions from the ferrocene, there was some degree of delocalization onto the Ni ion. Abstract : Heterobimetallic sandwich/half‐sandwich complex that underwent a reversible electrochemical oxidation and reduction at Fe and Ni sites, respectively. Reduction was localized at the Ni, while oxidation appeared to occur primarily at the Fe but the 4 K EPR spectrum showed two possible species some Ni III character.